2015
DOI: 10.1093/icvts/ivu446
|View full text |Cite
|
Sign up to set email alerts
|

Four-dimensional magnetic resonance imaging-derived ascending aortic flow eccentricity and flow compression are linked to aneurysm morphology

Abstract: Irrespective of aortic valve morphology and function, ascending aortic blood flow patterns are linked to distinct patterns of ascending aortic aneurysm morphology. Implementation of quantitative local blood flow analyses might help to improve aneurysm risk stratification in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Eccentric aneurysm was associated with a high level of flow compression (low flow compression index) irrespective of the underlining aortic valve morphology and function. These findings may indicate the potential diagnostic value of 4D flow MRI in clinical risk evaluation of patients with TAAs [30].…”
Section: Aortic Aneurysmmentioning
confidence: 70%
See 2 more Smart Citations
“…Eccentric aneurysm was associated with a high level of flow compression (low flow compression index) irrespective of the underlining aortic valve morphology and function. These findings may indicate the potential diagnostic value of 4D flow MRI in clinical risk evaluation of patients with TAAs [30].…”
Section: Aortic Aneurysmmentioning
confidence: 70%
“…Aortic dissection [23,28] Thoracic aortic aneurysm [29,30] Endoleak after endovascular aortic repair [31] Retrograde aortic flow as a potential source of embolic stroke [47] Bicuspid aortic valve [32,33,48] Coarctation of the aorta [ aortic diseases…”
Section: Aortamentioning
confidence: 99%
See 1 more Smart Citation
“…Like Dr Yurekli and colleagues [1], we were also concerned about different blood flow architectures within the tubular ascending aorta; however, when comparing convexity and concavity, the difference between BAV and TAV still remains, in the absence of a significant difference within each group (see Fig 2 in our paper [2]). In 2014, Kari and associates [4] demonstrated that the flow compression index was not significantly different in patients with aortic stenosis or regurgitation. The incidence of valve stenosis and regurgitation are significantly different between the groups, thus reflecting clinical everyday practice.…”
Section: Replymentioning
confidence: 99%
“…MMP-2 protein levels were observed to be higher in aortic regions with enhanced shear stress[18] and adaptive responses to high wall shear stress have been shown to be connected to pro—and activeMMP-2 in an animal mode l[19]. Wall shear stress in ascending aortic aneurysms was shown to increase with aortic diameter [20] and blood flow patterns in ascending aortic aneurysms seem to be associated with aortic morphology [21]. Taken together, these findings suggest that MMP-2 availability plays an important role in aortic wall pathology and that MMP-2 isoforms may serve as indicators of mechanical stress in the aortic wall.…”
Section: Introductionmentioning
confidence: 99%